Long-term follow-up in patients with gastric antral vascular ectasia (GAVE) after treatment with endoscopic band ligation (EBL) - Eccles, John; Falk, Vanessa; Montano-Loza, Aldo J.; Zepeda-Gómez, Sergio (Endoscopy International Open, 2019)
Background and study aims Gastric antral vascular ectasia (GAVE) is a capillary-type vascular malformation of the gastric antrum, usually diagnosed endoscopically in patients presenting with iron deficiency anemia or gastrointestinal bleeding. While there is established evidence for treatment with thermal modalities, such as argon plasma coagulation (APC) therapy, more recent studies have shown endoscopic band ligation (EBL) to be safe and effective in achieving remission. Our study aimed to evaluate long-term outcomes of patients with GAVE who underwent EBL at our institution. Patients and methods We retrospectively reviewed data from 33 patients with GAVE who underwent esophagogastroduodenoscopy and EBL between September 2012 and July 2017 within our institution, looking primarily at clinical response, recurrence, and blood transfusion requirements. Results Clinical response was achieved in 27 patients (81.8%). Among responders, recurrence-free survival decreased with time from 88 % at 1 year to 44 % at 2 years. Thirteen patients (48.1 %) had recurrence of GAVE at a mean time of 18.2 months (range 4.7 – 51.8). The only predictor of recurrence was greater number of pre-procedure blood transfusions. Conclusion This is the first study to evaluate long-term response and recurrence in patients with GAVE after treatment with EBL and predictors of clinical response after initial endoscopic therapy have been identified. While we were able to demonstrate excellent remission achievement rates in our GAVE patients who had undergone EBL, close clinical follow-up is clearly required as almost 50 % will have recurrence at around 18 months.